Evaluation of globins expression in brain, heart, and lung in rats exposed to side stream cigarette smoke - Tae, Barbara; Oliveira, Kelen Carneiro; Conceicao, Rodrigo Rodrigues da; Valenti, Vitor Engracia [UNESP]; Souza, Janaina Sena de; Laureano-Melo, Roberto; Sato, Monica Akemi; Barros Maciel, Rui Monteiro de; Giannocco, Gisele (Wiley-Blackwell, 2017)
The side stream cigarette smoke (SSCS) is a contributing factor in the pathogenesis of cigarette smoking-induced toxicity. Hemoglobin (Hb), myoglobin (Mb), neuroglobin (Ngb), and cytoglobin (Cygb) are globins with different distributions and functions in the tissues and have similar actions by providing O-2 (oxygen) for respiratory chain, detoxification of ROS and nitric oxide (NO), and protect tissues against irreversible lesions. We aimed to investigate the effects of SSCS exposure on gene and protein expression of Ngb, Cygb, and Mb in different tissue. The Ngb and Cygb gene and protein expression in the cerebral cortex increased after 1 week of rat exposure to SSCS. In hippocampus, the Ngb gene and protein expression increased after 1 week or more of exposure and no change was observed in Cygb gene and protein expression. In myocardium, Mb and Cygb gene expression increased at 1 and 4 weeks of exposure, while protein expression of both increased at 1, 2, 3, and 4 weeks. In lung, observed an increase in Cygb gene and protein expression after 2, 3, and 4 weeks of exposure. The findings suggest that SSCS modulates Ngb, Cygb, and Mb in central and peripheral tissue (c) 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1252-1261, 2017.
Keywords: cigarette smoke; cytoglobin; neuroglobin; myoglobin